Motivation Values For Learning Islam For Students In The Book Of Ta'lim Al-Muta'alim By Burhan Al-Din Al-Zarnuji - Ach Khusnan; M Toyib (JOSSE: Journal of Social Science and Economics, 2022)
Learning and learning is strongly influenced by a motivation. Students who have high learning motivation will be encouraged to focus more on the things that must be learned, so that maximum learning goals can be achieved. With high motivation, it will facilitate the learning process in achieving the desired goals. Motivation is very important because a group that has motivation will be more successful than a group that does not have motivation (less or unsuccessful learning). The concept of Islamic education has indeed represented the understanding of the expected educational goals, namely humanizing humans (humanization) which includes all aspects of humanity such as Intellectual Intelligence (IQ), Emotional Intelligence EQ, Spiritual Intelligence (SQ). One of the classic books about education is Ta'lim al-Muta'allim by Burhan al-Din al-Zarnuji. Al-Zarnuji is a medieval education figure who tries to provide a solution on how to create an education that is not only worldly oriented, but also oriented to the hereafter. The famous work of al-Zarnuji, namely Ta'lim al-Muta'allim, is one of the classic works in the field of education that has been widely studied and studied by educators, especially in Islamic boarding schools. The material of this book is loaded with spiritual moral education contents which, if realized and applied in daily life, of course the ideal goal of Islamic education can be achieved.